Astrocyte modulation of in vitro β-amyloid neurotoxicity - Paradisi, Silvia; Sacchetti, Benedetto; Balduzzi, Maria; Gaudi, Simona; Malchiodi-Albedi, Fiorella (Glia, 2004)
In Alzheimer's disease brain, β‐amyloid (Aβ) deposition is accompanied by astrocyte activation, whose role in the pathogenesis of the disease is still unclear. To explore the subject, we compared Aβ neurotoxicity in pure hippocampal cultures and neuronal‐astrocytic cocultures, where astrocytes conditioned neurons but were not in contact with them or Aβ. In the presence of astrocytes, neurons were protected from Aβ neurotoxicity. Neuritic dystrophy was reduced, synapses were partially preserved, and apoptosis was contrasted. The protection disappeared when astrocytes were also treated with Aβ, suggesting that Aβ‐astrocyte interaction is deleterious for neurons. This was supported by comparing Aβ neurotoxicity in pure neurons and neurons grown on astrocytes. In this case, where astrocytes were also in contact with Aβ, neuritic damage was enhanced and expression of synaptic vesicle proteins decreased. Our results suggest that astrocytes can protect neurons from Aβ neurotoxicity, but when they interact with Aβ, the protection is undermined and neurotoxicity enhanced. © 2004 Wiley‐Liss, Inc.